Progress: its Visionaries and its Malcontents. Issue 5 (4th July 2017) - Majumdar, Margaret A.; Chafer, Tony
Abstract : The introduction to this special issue on Progress: Its Visionaries and Its Malcontents sketches the background to contemporary debates about the concept of progress. It focuses particularly on the notion of political progress, or, in other words, a belief in the possibility of deliberate, concerted, collective action to change the world for the better. It traces how the notion of progress received a significant boost at the time of the European Enlightenment and then goes on to discuss some of the key fault lines in this thinking, most notably as it relates to imperialism and colonialism. In the face of a number of other recent critiques of progress, the importance of certain key historical periods, when progress was viewed in a more positive light and deemed to be a real, achievable goal, provides the rationale for the selection of essays chosen for this issue.